DYNAMIC MASKING DEPENDING ON SOURCE OF SNORING - ELLENBOGEN, Jeffrey M; KREMER, Kathleen Elizabeth; CARPENTER, Matthew Chace; PLETCHER, Steven Carl; LI, Chia-Ling (2024)
Aspects of the present disclosure provide methods, apparatuses, and systems for dynamically masking audible breathing noises determined to be generated by one or more sleeping partners. According to aspects, a subject's sleep is protected by detecting audible breathing noises in a sleeping environment, determining the audible breathing noises are not generated by the subject, and mitigating the perception of the audible breathing noises that are determined to originate from anther subject, such as a bed partner, pet, etc. The dynamic masking reduces the subject's exposure to unnecessary sounds and reduces the chances of masking sounds disturbing the subject's sleep.